PENERAPAN MEDIA APLIKASI CANVA DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS ANEKDOT PADA SISWA KELAS X A SMK NEGERI 7 BONE - Aidil Rahmat; Suhardiman; Ahmad Nurul Ihsan B (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a classroom action research that aims to determine the Implementation of Canva Application Media in Improving Anecdotal Text Writing Skills in Class X A Students of SMKN 7 Bone. The focus of this research is seen in the planning, implementation, and evaluation stages of learning specifically on writing in an effort to improve the Ability to Write Anecdotal Text Using the Canva Application in Class X A Students of SMKN 7 Bone which was carried out in two cycles. The results of the study show that the use of the Canva application can improve students' abilities in writing Anecdotal texts. The success of students in the learning process of writing Anecdotal texts can be seen in the classical completeness obtained by students who have reached 85% of students who get a score of 75 and above. In cycle I it reached 70% and increased in cycle II reaching 91% of students who get a score of 75 and above, so the percentage increase from cycle I to cycle II reached 21%. In addition, it can also be seen in the enthusiasm, activeness, seriousness, creativity, courage, and cooperation of students in carrying out each activity carried out.